Neurophysiological gradient in the Parkinsonian subthalamic nucleus as a marker for motor symptoms and apathy - Elena Bernasconi; Deborah Amstutz; Alberto Averna; Petra Fischer; Mario Sousa; Ines Debove; Katrin Petermann; Laura Alva; Andreia D. Magalhães; M. Lenard Lachenmayer; Thuy-Anh K. Nguyen; Michael Schuepbach; et al. (npj Parkinson's Disease)
Abstract Sensing-based deep brain stimulation should optimally consider both the motor and neuropsychiatric domain to maximize quality of life of Parkinson’s disease (PD) patients. Here we characterize the neurophysiological properties of the subthalamic nucleus (STN) in 69 PD patients using a newly established neurophysiological gradient metric and contextualize it with motor symptoms and apathy. We could evidence a STN power gradient that holds most of the spectral information between 5 and 30 Hz spanning along the dorsal-ventral axis. It shows elevated power in the sub-beta range (8-12 Hz) toward the ventral STN, and elevated dorsal beta power (16–24 Hz) indicative for the hemispheres contralateral to the more affected hemi-body side. The rigidity response to DBS was highest dorsally on the axis. Importantly, apathetic symptoms can be related to reduced ventral alpha power. In conclusion, the STN spectral gradient may inform about the motor and neuropsychiatric domain, supporting integrative closed-loop strategies.